The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.mcn.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine alters Homer1 natural antisense transcript in the nucleus accumbens

Abstract: Natural antisense transcripts (NATs) are an abundant class of long noncoding RNAs that have recently been shown to be key regulators of chromatin dynamics and gene expression in nervous system development and neurological disorders. However, it is currently unclear if NAT-based mechanisms also play a role in drug-induced neuroadaptations. Aberrant regulation of gene expression is one critical factor underlying the long-lasting behavioral abnormalities that characterize substance use disorder, and it is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(75 reference statements)
0
4
0
Order By: Relevance
“…We firstly identified DElncRNAs, DEmiRNAs and DEmRNAs in morphine addiction. Although these lncRNAs have not been reported to be involved in drug addiction, dysregulated expression of lncRNAs has been reported to play a critical role in the progression of addiction ( 26 , 27 ). Gao et al showed that upregulation of MEG3 was involved in morphine-induced autophagy in hippocampal neuronal HT22 cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…We firstly identified DElncRNAs, DEmiRNAs and DEmRNAs in morphine addiction. Although these lncRNAs have not been reported to be involved in drug addiction, dysregulated expression of lncRNAs has been reported to play a critical role in the progression of addiction ( 26 , 27 ). Gao et al showed that upregulation of MEG3 was involved in morphine-induced autophagy in hippocampal neuronal HT22 cells ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, a study revealed an increase in the expression of HOTAIRM1 in differentiating neurons, suggesting a role in early neurogenesis and brain development that may be disrupted by prenatal cocaine exposure (Lin et al, 2011). Another transcriptomic study also found an increase in Homer1 antisense (Homer1-AS) in the nucleus accumbens of mice after repeated cocaine exposure that in vitro was demonstrated to increase Homer1 sense expression (Sartor et al, 2017). Homer1 is an immediate-early gene and a scaffold protein found in postsynaptic densities that is associated with plasticity and spine morphogenesis (Shiraishi-Yamaguchi & Furuichi, 2007), meaning abnormal expression of Homer1-AS and subsequent dysregulation of Homer1 as a result of prenatal cocaine exposure may contribute to some of the abnormal neural development associated with prenatal cocaine exposure.…”
Section: Cocainementioning
confidence: 99%
“…Additionally, they found evidence that these corresponding changes in NAc lncRNA might correspond with changes in addiction-associated mRNA ( Zhu et al, 2016 ). Further research has characterized a specific lncRNA that is antisense to a synaptically localized addiction-related gene, Homer1 ( Sartor et al, 2017 ). After repeated injections of cocaine, it was found that Homer1-AS was increased within the NAc.…”
Section: Ncrna Regulation Of Substance Use Disorders (Suds)mentioning
confidence: 99%